Mechanisms Responsible for Sand Hazards Along Desert Highways and Their Control: A Case Study of the Wuhai–Maqin Highway in the Tengger Desert, Northwest China - An, Zhishan; Zhang, Kecun; Tan, Lihai; Niu, Qinghe; Wang, Tao (Frontiers in Environmental Science, 2022)
Highways in deserts usually suffer from severe sand hazards under the effect of wind-blown sand. In this article, the author has revealed the disaster-causing mechanisms of the Wuhai–Maqin Highway in the Tengger Desert, Northwest China. A sand control system with six belts was proposed and established for the highway, and its sheltering effect was examined through on-site monitoring. The results showed that from 2018 to 2019, the sand drift potential was dominated by northwest, northeast, and south winds, which indicated a low-energy windy environment, with a resulting southeast direction of sand transport. The particle size of surface sediments was mainly distributed between 1.26Φ and 2.5Φ, indicating fine sand and medium sand. The sand flux was mainly concentrated below 30 cm, accounting for 89.46% of the total sand transport. Airflow around the control system was significantly attenuated, with a maximum wind speed decreasing rate of 95.88%. The windproof efficiency of the control system against the near-surface wind-blown sand was more than 90%. This study provides a significant reference for the control of highway sand hazards in other deserts.